(untitled) (BIRDEM Medical Journal, 2018)
Pachydermoperiostosis (PDP) is a rare genetic disorder. Finger clubbing, skin changes and bony changes are the main three features of it. Here we present a 26-year-old male patient who was admitted for some other neurological disorder and diagnosed clinically as PDP. We diagnosed the condition clinically as gene analysis is not available in Bangladesh for a confirm diagnosis. Birdem Med J 2018; 8(2): 181-183